2015
DOI: 10.1097/md.0000000000000431
|View full text |Cite
|
Sign up to set email alerts
|

Age-Adjusted Charlson Comorbidity Index Scores as Predictor of Survival in Colorectal Cancer Patients Who Underwent Surgical Resection and Chemoradiation

Abstract: We studied the effect of Age-Adjusted Comorbidity Index Score in colorectal cancer patients who underwent similarly aggressive treatment.Using the National Health Insurance Research Database of Taiwan, we identified 5643 patients with colorectal cancer who underwent surgical resection and chemoradiation from 2007 through 2011. We estimated survival according to Age-Adjusted Comorbidity Index Scores and 5-year survival using Cox proportional hazard regression analysis, adjusting for sex, oxaliplatin-based chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 35 publications
2
57
0
Order By: Relevance
“…Univariate analysis revealed that both the OS and DFS of these samples were associated with age (P = 0.005; P = 0.006, respectively), tumor size (P = 0.028; P = 0.031, respectively), tumor location (P = 0.017; P = 0.020, respectively), pT stage (P = 0.004; P = 0.005, respectively), pN stage (P < 0.001), distant metastasis (P < 0.001), AJCC stage (P < 0.001), differentiation (P = 0.014; P = 0.015, respectively). Moreover, the multivariate analysis showed that only age (P = 0.004) and AJCC stage (P < 0.001) remained significantly independent prognostic factors, which was in accordance with other studies of large cohorts of CRC patients2324.…”
Section: Resultssupporting
confidence: 90%
“…Univariate analysis revealed that both the OS and DFS of these samples were associated with age (P = 0.005; P = 0.006, respectively), tumor size (P = 0.028; P = 0.031, respectively), tumor location (P = 0.017; P = 0.020, respectively), pT stage (P = 0.004; P = 0.005, respectively), pN stage (P < 0.001), distant metastasis (P < 0.001), AJCC stage (P < 0.001), differentiation (P = 0.014; P = 0.015, respectively). Moreover, the multivariate analysis showed that only age (P = 0.004) and AJCC stage (P < 0.001) remained significantly independent prognostic factors, which was in accordance with other studies of large cohorts of CRC patients2324.…”
Section: Resultssupporting
confidence: 90%
“…Muscle abnormalities, including low skeletal mass index (SMI, quantified as muscle cross‐sectional area adjusted by height squared, cm 2 /m 2 ) and low skeletal muscle radiodensity (SMD, quantified in Hounsfield units, HU), can be measured using computerized tomography (CT) images. Both these muscle abnormalities have been associated with the presence of specific co‐morbid conditions as well as cancer prognosis, and thus are potential mechanisms explaining why certain co‐morbid conditions are associated with worse cancer prognosis . Low SMI, also termed sarcopenia, is highly prevalent and has been shown as a strong prognostic factor in CRC patients and in many other types of cancer .…”
Section: Introductionmentioning
confidence: 99%
“…The Age-Adjusted Charlson Index to is a valid and reliable instrument; 118 however, it does not represent functional impairment, which could influence cancer screening, particularly in older adults. 119-121 Future studies should also include functional impairment.…”
Section: Discussionmentioning
confidence: 99%